Budaya Pembatalan: Hukuman dan Polisi Moral dalam Skandal Video Gisella Anastasia: Hukuman dan Polisi Moral dalam Skandal Video Gisella Anastasia - Wulandari, Nur Laily Wulandari; Kusumo Habsari, Sri (Universitas Negeri Surabaya, 2024)
This research analyzes the phenomena of social criticism and cancel culture in the context of the Gisella Anastasia sex scandal, focusing on analyzing netizen comments on YouTube news channels. Foucault's discourse analysis is used to explore how comments reflect power dynamics on social media. These comments fall into four categories: social media shaming, slut-shaming, redemption support, and superficial praise.The research findings show mixed reactions from netizens about the Gisella Anastasia scandal, with social media backlash and slut shaming highlighting strong criticism of her behavior.On the other hand, redemption support illustrates support and forgiveness towards the celebrity's efforts to amend their actions following clarification or apologies. Shallow praise focuses on compliments that are not related to the main issue.The research reveals that social media shaming and slut shaming are the primary comment categories. Using a Foucauldian approach, it examines how these comments reflect systems of discipline and punishment, highlighting the complexities of cancel culture and its impact on interpretation and judgment in the social media age.. The analysis of netizen comments provides insights into how power and social control are manifested in online interactions and their implications on the reputation and public perception of celebrities.